Analisis Faktor Yang Mempengaruhi Keputusan Pembelian Sepatu Pada Soccer Corner Di Kota Bandarlampung - Lestari Wuryanti; Amir Nurdiyanto (Universitas Malahayati, 2019)
The purpose of this study was to determine the effect of products, promotions, prices, andlocation on purchasing decisions at Soccer Corner, Bandar Lampung. This research wasconducted at the Bandar Lampung Soccer Corner. The population in this study was 365 andthe sample in this study was 191 samples. Sampling in this study using the NonprobalitySampling method with purposive sampling technique. The results of this study indicate thatproducts, promotions, prices and locations have a positive and significant effect onpurchasing decisionsKeywords: Effect of product, promotion, price and location on purchasing decisions